Interaction-induced double-sided skin effect in an exciton-polariton system - Xu, Xingran (2022)
The non-Hermitian skin effect can be realized through asymmetric hopping between forward and backward directions, where all the modes of the system are localized at one edge of a finite 1D lattice. Here we show theoretically that in a finite chain of 1D exciton-polariton micropillars with symmetric hopping, the inherent nonlinearity of the system can exhibit a double-sided skin (bi-skin) effect based of the fluctuations of the system, where the modes of the system are localized at the two edges of the system. To show the topological origin of such modes, we calculate the winding number. The bi-skin effect can be detected experimentally as an intensity drop at one edge of the chain and an increase at the opposite edge upon an increase of the polariton density under continuous wave excitation.